Factors associated with actively working in the very long-term following acute coronary syndrome (Clinics, 2021)
OBJECTIVES: Returning to work after an episode of acute coronary syndrome (ACS) is challenging for many patients, and has both personal and social impacts. There are limited data regarding the working status in the very long-term after ACS. METHODS: We retrospectively analyzed 1,632 patients who were working prior to hospitalization for ACS in a quaternary hospital and were followed-up for up to 17 years. Adjusted models were developed to analyze the variables independently associated with actively working at the last contact, and a prognostic predictive index for not working at follow-up was developed. RESULTS: The following variables were significantly and independently associated with actively working at the last contact: age4median (hazard-ratio [HR], 0.76, po0.001); male sex (HR, 1.52, po0.001); government health insurance (HR, 1.36, po0.001); history of angina (HR, 0.69, po0.001) or myocardial infarction (MI) (HR, 0.76, p=0.005); smoking (HR, 0.81, p=0.015); ST-elevation MI (HR, 0.81, p=0.021); anterior-wall MI (HR, 0.75, p=0.001); non-primary percutaneous coronary intervention (PCI) (HR, 0.77, p=0.002); fibrinolysis (HR, 0.61, po0.001); cardiogenic shock (HR, 0.60, p=0.023); statin (HR, 3.01, po0.001), beta-blocker (HR, 1.26, p=0.020), angiotensinconverting enzyme (ACE) inhibitor/angiotensin II receptor blocker (ARB) (HR, 1.37, p=0.001) at hospital discharge; and MI at follow-up (HR, 0.72, p=0.001). The probability of not working at the last contact ranged from 24.2% for patients with no variables, up to 80% for patients with six or more variables. CONCLUSIONS: In patients discharged after ACS, prior and in-hospital clinical variables, as well as the quality of care at discharge, have a great impact on the long-term probability of actively working.